Zero-field Hall effect emerging from a non-Fermi liquid in a collinear antiferromagnet V1/3NbS2 - Mayukh Kumar Ray; Mingxuan Fu; Youzhe Chen; Taishi Chen; Takuya Nomoto; Shiro Sakai; Motoharu Kitatani; Motoaki Hirayama; Shusaku Imajo; Takahiro Tomita; Akito Sakai; Daisuke Nishio-Hamane; et al. (Nature Communications)
Abstract Magnetically intercalated transition metal dichalcogenides (TMDs) provide a versatile three-dimensional (3D) material platform to explore quantum phenomena and functionalities that emerge from an intricate interplay among magnetism, band structure, and electronic correlations. Here, we report the observation of a nearly magnetization-free anomalous Hall effect (AHE) accompanied by non-Fermi liquid (NFL) behavior and collinear antiferromagnetism (AFM) in V1/3NbS2. Our single-crystal neutron diffraction measurements identify a commensurate, collinear AFM order formed by intercalated V moments. In the magnetically ordered state, the spontaneous AHE is tenfold greater than expected from empirical scaling with magnetization, and this strongly enhanced AHE arises in the NFL regime that violates the quasiparticle picture. V1/3NbS2 challenges the existing single-particle framework for understanding AHEs based on one-body Berry curvature and highlights the potential of magnetically intercalated TMDs to unveil new electronic functionalities where many-body correlations play a critical role.